The ocular health and visual function status of sewing professionals of garment factories of Kathmandu Valley - Sharma, Sadhana; Kharel Sitaula, Ranju; Mishra, Sanjeeb; Shrestha, Gulshan Bdr; Sharma, Anand Kumar (Cogent medicine, 2021)
Sewing professionals are engaged in extensive near work in a small and intensely condensed workspaces, thereby exposing themselves to different ocular and vision-related problems. In a cross-sectional study, 305 sewing professionals of garment factories were included and assessed for ocular and vision-related problems. The assessment included detailed anterior and posterior segment examination and vision assessment comprising of visual acuity, static refraction, dynamic refraction, eye alignment, convergence, fusional vergence, amplitude of accommodation, accommodative facility, color vision, and stereopsis. The findings were recorded on preset proforma and data were analyzed in SPSS version 20. Ocular and Vision-related problems were reported for all participants by descriptive data (number, frequency, median, IQR). The median age of the sewing professional was 30 (24-39) years with male predominance (65.2%). On anterior segment assessment, meibomitis (24.26%) was the most prevalent anterior segment disorder. Prevalence of refractive error was seen in 79.7% of the subjects of which hyperopia (44.5%) was the most prevalent form of refractive error. In participants of age group less than 40 years, 79.5% of the population were found to be consistent with some form of vergence and accommodative disorder; 44.5% manifesting convergence excess with accommodative insufficiency. These participants reported ocular, visual, and asthenopic symptoms at a higher rate as compared to other dysfunctions. Association between vision-related problems and symptoms was analyzed using a Chi-square test. A significance level of 0.05 was applied for a 95% confidence interval. Ocular, visual, and asthenopic symptoms were significantly associated with binocular and accommodative disorders (r = 18.726, p = 0.04). Ocular morbidity and binocular vision anomalies were significantly prevalent in sewing professionals of garment factories.